Calcitonin Gene-Related Peptide Is an Important Regulator of Cutaneous Immunity: Effect on Dendritic Cell and T Cell Functions - Norihisa Mikami; Hiroaki Matsushita; Tetsuya Kato; Rumi Kawasaki; Taichi Sawazaki; Taeko Kishimoto; Ogitani Yusuke; Keiko Watanabe; Yayoi Miyagi; Kaori Sueda; So‐ichiro Fukada; Hiroshi Yamamoto; et al. (2011)
Abstract Some cutaneous inflammations are induced by percutaneous exposure to foreign Ags, and many chemical mediators regulate this inflammation process. One of these mediators, calcitonin gene-related peptide (CGRP), is a neuropeptide released from nerve endings in the skin. CGRP binds to its receptors composed of receptor activity-modifying protein 1 and calcitonin receptor-like receptor to modulate immune cell function. We show that CGRP regulates skin inflammation under physiological conditions, using contact hypersensitivity (CHS) models of receptor activity-modifying protein 1–deficient mice. CGRP has different functions in CHS responses mediated by Th1 or Th2 cells; it inhibits Th1-type CHS, such as 2,4,6-trinitrochlorobenzene–induced CHS, but promotes Th2-type CHS, such as FITC-induced CHS. CGRP inhibits the migration of Langerin+ dermal dendritic cells to the lymph nodes in 2,4,6-trinitrochlorobenzene–induced CHS, and upregulates IL-4 production of T cells in the draining lymph nodes in FITC-CHS. These findings suggest that CGRP regulates several types of CHS reactions under physiological conditions and plays an important role in cutaneous immunity.